PTCA-Funded Public Preschools: Basis for Adopt-A-Preschool Program - Opina, Ma. Fe D. (JPAIR Multidisciplinary Research, 2009)
LDCU was awarded for having the most outstanding community extension program. Thus, the researcher conducted this study to determine the institutional capability of three selected PTCA funded public preschools which have been operating for five years in the rural areas of Cagayan de Oro City. Adopting a community extension preschool program as an output of the study is based on school capabilities focused on management, faculty, parents, learning activities and experiences, and physical environment. Profile of parent respondents concerning monthly family income, occupation, and preschool involvement helped in the preschool assessment. Significant differences in the responses involving the five capability criteria helped identify the preschool that would be adopted as a pilot school. Having used the descriptive-evaluative method, the qualitative and quantitative aspects were considered to determine the institutional capabilities of the selected PTCA funded public preschools. Study evaluators were parents, teachers, and school administrators. Three sets of instruments were used based on Department of Education standards and previous studies. These were incorporated on the institutional capabilities of preschool, parent involvement, and interview schedule. The research tools made possible the in depth study for possible improvement of the existing preschools.
Keywords: parents involvement; preschool; community extension